Whole Blood Interferon γ Release Is a More Sensitive Marker of Prior Exposure to Coxiella burnetii Than Are Antibody Responses - Scholzen, Anja; de Vries, Margot; Duerr, Hans-Peter; Roest, Hendrik-Jan; Sluder, Ann E.; Poznansky, Mark C.; Kouwijzer, Milou L. C. E.; Garritsen, Anja (Frontiers in Immunology, 2021)
For the zoonotic disease Q fever, serological analysis plays a dominant role in the diagnosis of Coxiella burnetii infection and in pre-screening for past exposure prior to vaccination. A number of studies suggest that assessment of C. burnetii-specific T-cell IFNgamma responses may be a more sensitive tool to assess past exposure. In this study, we assessed the performance of a whole blood C. burnetii IFNgamma release assay in comparison to serological detection in an area of high Q fever incidence in 2014, up to seven years after initial exposure during the Dutch Q fever outbreak 2007-2010. In a cohort of >1500 individuals from the Dutch outbreak village of Herpen, approximately 60% had mounted IFNgamma responses to C. burnetii. This proportion was independent of the Coxiella strain used for stimulation and much higher than the proportion of individuals scored sero-positive using the serological gold standard immunofluorescence assay. Moreover, C. burnetii-specific IFNgamma responses were found to be more durable than antibody responses in two sub-groups of individuals known to have sero-converted as of 2007 or previously reported to the municipality as notified Q fever cases. A novel ready-to-use version of the IFNgamma release assay assessed in a subgroup of pre-exposed individuals in 2021 (10-14 years post exposure) proved again to be more sensitive than serology in detecting past exposure. These data demonstrate that C. burnetii-induced IFNgamma release is indeed a more sensitive and durable marker of exposure to C. burnetii than are serological responses. In combination with a simplified assay version suitable for implementation in routine diagnostic settings, this makes the assessment of IFNgamma responses a valuable tool for exposure screening to obtain epidemiological data, and to identify previously exposed individuals in pre-vaccination screens.